Comment un État libéral peut-il être à la fois neutre et paternaliste? - Merrill, Nathaniel Roberto Buil (2011)
In this article I defend that liberal perfectionism, even when paternalistic, is compatible with state neutrality. I defend this compatibility as follows. First, I distinguish three types of neutrality. Then, I distinguish three types of paternalism. I then examine under what conditions neutrality and paternalism can be compatible. Finally, I argue that neutrality of consequences, which seems to be the most demanding version of neutrality, is also compatible with paternalism and will conclude by suggesting that the only way to make paternalism and neutrality incompatible is to require that neutrality encompasses at the same time neutral justifications, aims, and consequences.